Juridical Analysis of Online Gambling as a Challenge to Realizing Inclusive Digital Transformation in Indonesia (Universitas Terbuka, 2025)
In the era of rapid digital transformation, digital inclusivity has become a crucial pillar of national development, ensuring equitable access to technology for all members of society. However, the widespread phenomenon of online gambling in Indonesia poses a serious challenge to achieving this goal. This study aims to juridically analyze online gambling practices as a structural barrier to realizing inclusive digital transformation. Using a normative legal research method with conceptual and statutory approaches, this study examines the weaknesses in the existing legal framework, particularly in the implementation of the ITE Law and the Criminal Code. It also evaluates law enforcement challenges in the context of transnational and anonymous cybercrimes. The analysis shows that overlapping regulations, limited international cooperation, insufficient monitoring technology, and low public digital literacy are the main obstacles in combating online gambling. Furthermore, the predominantly repressive legal approach is deemed inadequate to meet the need for a safe and inclusive digital transformation. Therefore, adaptive and collaborative regulatory reform is necessary, including strengthening digital literacy, establishing a protection system for vulnerable groups, and enhancing inter-agency and international cooperation. This study recommends a more holistic digital legal policy reform as a foundation for creating a digital ecosystem that is fair and free from the threat of online gambling.